Determinant of Antiretroviral Therapy Adherence Through the Health Belief Model Theory in People Living with HIV/AIDS: A Systematic Review - Supriyatni, Nani; Sumiati, Tati; Lestari, Tutik; Andiani, Andiani (GLOBAL HEALTH SCIENCE GROUP, 2024)
Human Immunodeficiency Virus (HIV) and Acquired immunodeficiency syndrome (AIDS) are still threats to public health. Indonesia ranks third highest in the number of people living with HIV/AIDS (PLWHA) and new infection cases in the Asia-Pacific region after India and China. One of the sustainable development targets to improve health and well-being is to end the AIDS epidemic by 2030 which refers to the global policy of